Women leadership: a case study in the Otjozondjupa Region, Namibia - Araes, Cornelia (Rhodes University, Faculty of Education, Department of Education, 2012)
Empowerment of women in leadership and in particular, school leadership has been the focus of the Namibian government and the country since independence in 1990. Different policies and laws, post" independence, make provision for women empowerment and leadership in a range of organisations and institutions throughout the country. However, reports on gender equity in leadership positions suggest that Namibia is not really moving towards these policy goals at a sufficiently quick pace. A lot still needs to be achieved in terms of transforming the gender stereotyping in Namibia, which still suffers from the legacy of gender discrimination of the apartheid era. Modern" day academic authors and journalists portray an increasing interest in an awareness of the advantages of women leadership. Women are increasingly perceived to have leadership styles more suitable for contemporary conditions than men. It is against this backdrop that this study sought to investigate women leadership in the Otjiwarongo circuit in the Otjozondjupa educational region in Namibia. The study used a qualitative, interpretive research paradigm. It adopted a case study approach. The primary participants consisted of four women principals in the Otjiwarongo circuit and the secondary participants included four women education officers from the same circuit. Semi" structured interviews, a focus group interview and observation were applied as methods for collecting data and the data collection period was just over six weeks. Data analysis was done through coding and identification of categories. The findings revealed that women principals possessed the qualities of commitment, good communication and are passionate about their work, which are qualities normally associated with effective leadership. In terms of their role in their schools, they emerged as democratic leaders who involved all stakeholders in the decision making process through consensus. In addition, they demonstrated distributive and servant leadership in their interactions with stakeholders. The main challenge to the leadership position of these women principals seemed to be the stereotypical view held, that as women, they had to work twice as hard as men at leading schools. The study recommended that people oriented leadership styles, such as the ones enacted by the women principals in this study, are highly recommended for effective leadership in the 21st century.
Keywords: Women -- Education (Primary) -- Namibia; Leadership in women -- Education (Primary) -- Namibia; Management -- Education (Primary) -- Namibia; Educational leadership -- Namibia